Comparing direct and imagined intergroup contact among children: Effects on outgroup stereotypes and helping intentions. (November 2015) - Vezzali, Loris; Stathi, Sofia; Crisp, Richard J.; Capozza, Dora
Abstract: We conducted an experimental intervention aimed at comparing the effectiveness of direct and imagined intergroup contact. Italian elementary school children took part in a three-week intervention with dependent variables assessed one week after the last intervention session. Results revealed that direct and imagined intergroup contact, compared to control conditions of direct and imagined intragroup contact, had an additive impact when it came to reducing negative stereotypes of immigrants and fostering future helping intentions toward this group. The theoretical and practical implications of the findings are discussed.